Monitoring training load and perceived recovery in female basketball: implications for training design - Sansone, P.; Tschan, H.; Foster, C.; Tessitore, A. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the relationship between internal training load and perceived recovery of semi-professional female basketball players during the competitive season. Eleven female players were monitored for 14 weeks during the in-season phase. For each event (training and game), data were collected as follows: (a) Total Quality Recovery (TQR) score before the event (TQRpre); (b) session Rating of Perceived Exertion (sRPE) 20 minutes after completion of the event, to calculate training load (s-TL) of the event; and (c) TQR scores 12 (TQRpost12) and 24 hours (TQRpost24) after the event. Data were analyzed for daily, weekly, and mesocycle (regular season; regional play-off; and national play-off) time frames. Daily analysis showed that: TQRpost12 was lower than TQRpre (p < 0.001) and TQRpost24 (p < 0.001); s-TL had a moderate negative correlation with TQRpost12 (r = -0.48, p = 0.002); the difference between TQRpre and RPE (TS-Delta) had a very large positive correlation with TQRpost12 (r = 0.70, p < 0.001); and TQRpost24 was not significantly correlated with training parameters. Weekly analysis highlighted a very large negative correlation between the acute:chronic workload ratio and TQR collected at the start of the following week (TQRfw) (r = -0.86, p < 0.001). Finally, although weekly TL and TQRfw did not differ between mesocycles, their correlation increased in the later seasonal phases. This study demonstrated negative relationships between training load and recovery of semi-professional female basketball players at daily, weekly, and mesocycle levels. Therefore, concurrently monitoring training and recovery with the sRPE method and TQR scale is recommended for designing training schedules in basketball.